Sistema de Monitoreo de Nivel de Líquido en Grandes Depósitos - Quiala Llorens, Reinier; Pérez Molinet, Ailén; Hernández Montero, Fidel Ernesto (Ingeniería, 2019)
Context: The objective of this work is to design and build a system capable of controlling the level of liquids stored in large tanks. The system is also oriented to its use in automatic control practices and the transmission of information from a distance. Method: It consists of different stages that meet the fulfillment of the proposed objective. In addition, it is composed of sound and light alarms in case of spills in the tanks or lack of communication between its components. The realization of digital control within the system required a data acquisition procedure implemented by Arduino with XBee modules for communication, and a personal computer. Results: This type of procedure to implement the control was chosen due to the ease of implementation, the benefits and the low costs of the system with respect to those existing in the market. Another task was the practical study of the different control techniques applied to a real system for monitoring the level of liquids in large capacity tanks. Conclusions: The validation of the measurement system was made through a comparison between the real values obtained with the measurement instruments and the values shown by the system through the web application that was designed. The correct operation of this system allowed its subsequent installation in real deposits.